AN INVESTIGATION OF TEACHERS APPROACHES EMPLOYED IN TEACHING THE ENGLISH LITERATURE: OBSERVATION OF EFL CLASSROOM AT SMK PURNAMA WONOSOBO - Annisa Salsabila; Sahid Sahid (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2024)
This article presents an investigation into the approaches employed by teachers when teaching English literature in EFL (English as a Foreign Language) classrooms. The study aims to explore the instructional strategies utilized by teachers and their potential impact on student engagement and comprehension. Through systematic observations conducted within authentic classroom settings, this research provides valuable insights into effective pedagogical practices for teaching English literature in an EFL context. However, there is limited research specifically focusing on teacher approaches within EFL classrooms when it comes to teaching English literature. To address this gap, qualitative methods were employed with naturalistic observations carried out in multiple EFL classrooms. The expected findings shed light on various instructional techniques employed by teachers while teaching English literature topics in EFL contexts. These may include close reading exercises, group discussions, and integration of multimedia resources to facilitate interactive learning experiences related to English literature. By investigating these approaches through observation-based research methods, this study contributes to the existing body of knowledge regarding effective pedagogy for teaching English literature in an EFL setting. Overall, this investigation emphasizes the importance of understanding teacher approaches when delivering instruction on English Literature for learners studying it as a foreign language. It serves as a resourceful guide for educators aiming to optimize student engagement and comprehension levels while fostering appreciation for literary works across cultures within an EFL classroom.